Avaliação in vitro e in silico do efeito vasorelaxante de um novo complexo de rutênio (FOR611A) em anéis de aorta isolados de ratos wistar normotensos - Braz, Helyson Lucas Bezerra (2022)
Cardiovascular diseases are the diseases that kill the most in the world and endothelial dysfunction is a problem that is intrinsically related to the formation of these diseases. Endothelial dysfunction occurs when vasoconstrictor effects overlap with vasodilator effects. Knowing this, the pathway involving nitric oxide, soluble guanylate cyclase and cyclic GMP (NO-sGC-cGMP) is well evidenced in vasodilation and several studies have shown that ruthenium-containing compounds have great interaction effects in this biological pathway. Thus, the objective of this work was to evaluate the vasodilatory effect of the rutheniumcontaining molecule (FOR611A) in isolated aortic fragments from Wistar rats, in order to clarify its mechanism of action. As results attributed to the methodology of this work, the vasodilator effect of FOR611A was verified in the aorta artery, with intact endothelium, precontracted with KCl (60 mmol/L) or phenylephrine (PHE) (1 µmol/L), compared to the control positive (sodium nitroprusside - SNP) and negative control (dimethylsulfoxide - DMSO). In the evaluation of the mechanism of action of FOR611A, the influence of the endothelium was verified, as well as the interference of incubation with inhibitors (L-NAME, hydroxocobalamin, L-cysteine, ODQ, tetraethylammonium, glibenclamide, 4-AP and barium chloride) on NO and K+ channel pathways of muscle relaxation. In addition, the network of biological processes of the pathways that act on vasodilation was built and the molecular docking test of FOR611A was performed with the main targets of these pathways. In the reactivity tests, it was possible to verify the vasodilation of FOR611A, which showed the results of the EC50 of 1.07 µg/mL (95%CI: 0.82 - 1.40) and the EMAX was 118.20% ± 3.43 with dilation superior to DMSO and statistically similar to SNP. It was possible to verify that the absence of the endothelium had no influence on the results. In preparations with different inhibitors, only L-NAME and ODQ showed a significant reduction in EMAX, resulting in 86.49 ± 8.07% and 66.37 ± 9.41%, respectively. In the networks of interactions, it was possible to identify that the guanylate cyclase subunit A3 (GUCY1A3) is the region with the highest number of participations in the processes of vasodilation. In addition, docking confirmed the interaction of the FOR611A structure with GUCY1A3 and also with eNOS. Therefore, the results found suggest that FOR611A causes an endothelium-independent vasodilator effect, participating in the activation of the eNOS/GUCY1A3 pathway.